Self-assembly of copper nanoclusters: isomeric ligand effect on morphological evolution. Issue 19 (1st September 2021) - Kolay, Sarita; Maity, Subarna; Bain, Dipankar; Chakraborty, Sikta; Patra, Amitava
Abstract : Uncovering the chemistry behind the self-assembly of copper nanoclusters: cuprophilic, π–π stacking, and agostic interactions are elicited to arrange into ordered rods, platelets, and ribbon-like structures. Abstract : Tailoring the hierarchical self-assembly of metal nanoclusters (NCs) is an emergent area of research owing to their precise structure and flexible surface environment. Herein, the morphological evolution from rods to platelets to ribbon-like structures through self-assembly of Cu7 NCs is dictated by the positional isomerism of the surface capping ligand, dimethylbenzenethiol (DMBT). Besides cuprophilic interaction, the interplay between π–π stacking and agostic interaction (Cu⋯H–C) directs the inter-NC organization into different ordered architectures. The excited-state relaxation dynamics of the red phosphorescent assembled structures has been correlated with their compactness and the degree of bonding interactions present.